Impact of 'Poor' data correction to network-RTK user - Shariff, Noor Suryati; Musa, Tajul Ariffin; Ses, Shahrum; Lim, Samsung (2008)
The network-RTK is being utilized to reduce distance-dependent errors and thus improve the long-range carrier phase ambiguity resolution. The accuracy of position has claimed in centimeter-level, which is proportionally to the quality of correction received. However there are some cases in modeling of the network correction where poor raw data quality are used that resulting in the poor correction transmitted to the user. The user just accepts the uncertainty of the true corrections without knowing the quality of the corrections. Hence, this research is aimed to study the impact of poor network correction to the estimated parameters of interest on network users receiver. Preliminary result has shown that by ignoring the poor network corrections can provide better estimate of the network users position.